Esensi Nilai Ummatan Wasathan sebagai Modal Hidup di Era New Media - Nadea Siti Sa’adah (Gunung Djati Conference Series, 2022)
The new media era has become an era that is widely echoed by the wider community which has many effects, both positive and negative. This study aims to discuss the essence of the wasathan ummatan value as a living capital in the new media era. This study uses a qualitative method based on a literature study that uses content analysis. The results and discussion show the frenzy of the new media era which is currently being "frenzied". Rumors, gossip, extreme thoughts have sprung up a lot. So that religious moderation is needed which in the language of the Qur'an is called ummatan wasathan. So this study concludes that Ummatan wasathan is a way to be able to show the direction and path of goodness, which is balanced by an attitude of tawazun (balanced) that can reconcile one people to each other. This research is still far from perfect. The limitation in this study is the lack of interpretation from other references, so the authors recommend further research on this matter.